Analisis Pengaruh Good Corporate Governance, Strategi Diferensiasi Dan Corporate Social Responsibility Terhadap Kinerja Keuangan (Studi Pada Perusahaan Pariwisata, Restaurant dan Hotel Yang Terdaftar di BEI Tahun 2013-2015) - Mirsa, Mesik; , Zulfa Irawati, S.E., M.Si (2017)
This research is meant to know the influence of Good Corporate Governance which is dimention by the Ownership of Institutional, the Audit Committee, the Board of Direction, Leverage, Differentiation of Strategy which is dimention the which is dimention by the Operation Expenses and the Size Firm, Corporate Social Responsibility to the Financial Performancce. The hyphotesis of this research is Good Corporate Governance, Differentiation of Strategy and Corporate Social Responsibility are significant influence on the Financial Performance. The population of this research is Travel, Restaurant and Hotel companies listed in the Bursa Efek Indonesia for the year 2013 until 2015. The method of the research is purposive sampling with some criteria has determined the sum of sample is 36 samples. The data used secondary data from Indonesia Stock Exchange (IDX) and Annual Report for year 2013 until 2015. The data was analyzed using is linier multiple regression with SPSS 16 program. In based the result of the research shows that Good Corporate Governance variable which is dimention by the Ownership of Institutional, the Audit Committee, and the Board of Direction are not significant influence on the Financial Performance however Leverage is significant influence on the Financial Performance, Differentiation of Strategy variable which is dimention by the Operation Expenses and the Size Firm are significant influence on the Financial Performance. Corporate Social Responsibility variable is significant influence on the Financial Performance.